Peranan Promosi dan Kemudahan Penggunaan di Dalam Keputusan Bertransaksi Menggunakan Isaku pada Konsumen Indomaret di Kecamatan Cileungsi - Ayoung Megantara; Widiana Indah Permata (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the role of promotion and ease of use in transaction decisions using Isaku for Indomaret consumers in Cileungsi sub-district. This study uses descriptive qualitative research methods. The informants in this study were 10 Indomaret consumers who were loyal consumers and Isaku users. The data collection methods used are observation, interviews, and documentation. The data collected were analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of research conducted by conducting interviews show that the role of promotion and ease of use is very important and is the main reason in the decision to transact using Isaku for Indomaret consumers in Cileungsi sub-district, indicated by the promotional message conveyed by Indomaret through the Isaku application is very interesting, consumers are helped by the media provided by Indomaret through the Isaku application, the promotional period provided by Indomaret through the Isaku application is quite varied in time, consumers often transact using the Isaku payment media, consumers feel quite familiar with the Isaku payment method because it is easy to learn, consumers easily get the Isaku application with smart phone devices and the Isaku application is easy to operate for new users. Keywords: Promotion, Ease of Use, Transaction Decision